Analisis Korelasi Kanonik Hubungan Lingkungan Pendidikan terhadap Prestasi Belajar - Riski Dwi Rianto Putra; Atus Armadi Purta; Riry Sriningsih (Journal of Mathematics UNP, 2021)
Abstract – The learning achievement is the result of learning achieved in the form of value. Environmental education is one of the factors that influence learning achievement. To see the relationship between environmental education with student achievement SMP Lanud Padang used statistical analysis canonical correlation analysis. Canonical correlation analysis is used to see the relationship between dependent variables with independent variables. The results showed that the relationship between environmental education with student achievement class VII Space Lanud Padang can not be known, because the analysis could not proceed to the stage interpretation of the canonical variables. However, based on the value of the P-Value between environmental variables and the variables education learning achievement can be seen learning achievement is affected by a significant educational environment, including PAI, PKN, Indonesian and English. And school environments have the most impact on student learning in junior high presatasi Space Lanud Padang. Keywords – Learning achievement, environmental education, canonical correlation analysis